Representasi tindak tutur netizen dalam kasus mahasiswa UIN sultan syarif kasim riau di media sosial: perspektif pragmatik austin - Jail keni Aguselin Sembiring; Berlian Serevina Harianja; Jufrikhan Manca Nurrin; Sri Lestari Putri Mulyani Harahap; Sherli Ramadhani; M. Oky f. Gafari; Herning Puspitarini (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to examine the types of speech acts found in netizen comments on the social media platform TikTok related to the Fara and Reyhan case. The virality of the case illustrates that social media functions not only as a medium for disseminating information but also as a platform for shaping public opinion through language. This study used a qualitative approach with descriptive methods and adopted J.L. Austin's speech act theory, which encompasses locutionary, illocutionary, and perlocutionary acts. The data analyzed consisted of netizen comments collected from TikTok videos discussing the case. The research findings indicate that locutionary speech acts play a role in conveying information or opinions explicitly without hidden meanings. Illocutionary speech acts are used to express specific intentions, such as providing support, criticism, suggestions, and demonstrating partisanship. Meanwhile, perlocutionary speech acts demonstrate the impact or effect felt by the reader, such as the emergence of sympathy, fear, or a specific evaluation. Overall, the results of this study confirm that netizen comments on social media play a significant role in shaping public views of an event. Therefore, it is important to raise awareness of language use and digital literacy so that communication on social media can be more tactful and constructive